Characterization of the Thermophilic Bacterium Geobacillus Sp. Strain gwe1 Isolated from a Sterilization Oven - Blamey-Alegria, J (2013)
A gram-positive, rod-shaped, spore-forming, motile thermophilic bacterium was isolated from a sterilization oven. The microorganism GWE1, formally named Geobacillus wiegelii identified as a member of the genus Geobacillus. GWE1 grew under aerobic conditions of between 60-80°C (optimum 70°C), in a pH range of 3.0-8.0 (optimum pH70°C 5.8), and between 0 and 2 M NaCl (optimum 0.3 M). The membrane polar lipids were dominated by branched saturated fatty acids, which included as the major constituents; iso-15:0 (13.3%), 16:1(?7) (12.8%), 16:0 (28.5%), iso-17:0 (13.5%) and anteiso-17:0 (12.3%). The DNA G+C content was 47.2 mol% (determined by HPLC). The 16S rRNA gene sequence of GWE1 showed a high similarity with Geobacillus caldoxylosilyticus (97%). However, the level of DNA-DNA relatedness was only 58%. These data suggest that GWE1 is probably a novel specie of the genus Geobacillus. © 2013, The Korean Society for Microbiology and Biotechnology.